Adolescents' perception of the severity of binge eating disorder: a population-based study. (2nd January 2016) - Anderson, Rebecca; Gratwick-Sarll, Kassandra; Bentley, Caroline; Harrison, Carmel; Mond, Jonathan
Abstract: Background : Binge eating disorder (BED) is relatively common in young people and is associated with marked impairment in physical and mental health. Aims : We examined perceptions of the severity of BED in a population-based sample of adolescents. Methods : Male ( n  = 531) and female ( n  = 1135) adolescents recruited from 12 Australian schools completed a survey that featured a vignette of a fictional female school student suffering from BED followed by a series of questions addressing perceptions of severity. Results : Approximately half of participants agreed or strongly agreed that BED is a serious problem (male: 52.0%; female: 63.2%) requiring professional treatment (male: 48.2%; female: 54.5%). Approximately one-third of boys (30.7%) believed that BED is primarily a problem of "lack of will power/self-control", whereas one in five girls (19.3%) held this view. Less than half of participants (male: 42.7%; female: 44.1%) believed that someone with BED would be deserving of sympathy. Conclusion : The findings suggest that many adolescents, boys in particular, do not consider BED to be a serious mental health problem and believe that individuals with BED lack will-power and/or are undeserving of sympathy. Awareness and understanding of BED may need to be addressed in school-based mental health promotion programs.